A magnetically separable acid-functionalized nanocatalyst for biodiesel production - Changmai, Bishwajit; Wheatley, Andrew E.H.; Rano, Ruma; Halder, Gopinath; Selvaraj, Manickam; Rashid, Umer; Rokhum, Samuel Lalthazuala (Elsevier, 2021)
A robust, magnetically recoverable Fe3O4@SiO2-SO3H core@shell nanoparticulate acid catalyst was successfully synthesized by a stepwise co-precipitation, coating, and functionalization. It was utilized as a heterogeneous catalyst for the transesterification and esterification of triglycerides and free fatty acids in Jatropha curcas oil (JCO) to a fatty acid methyl ester (FAME) mixture. This product conformed to ASTM standards for biodiesel. The as-prepared catalyst had a magnetic saturation of 30.94 emu g−1, surface area of 32.88 m2g−1, acidity of 0.76 mmol g−1, and pore diameter of 3.48 nm. The catalyst showed 98 ± 1% conversion using the optimized reaction conditions of methanol:oil molar ratio of 9:1, 8 wt% catalyst loading, 80 °C, and 3.5 h. The transesterification of JCO to FAME using the present catalyst benefitted from a very low activation energy of 37.0 kJ mol−1. The solid acid catalyst exhibited excellent chemical and thermal stability, and also reusability based on easy separation from the reaction mixture due to its inherently magnetic nature. Modest deterioration in oil conversion after multiple uses was offset by one-pot, quantitative regeneration of catalyst active sites. This enabled identical performance in JCO methyl transesterification and esterification in the 1st and 10th catalytic cycles.